Radikalisme dan Gerakan Dakwah - Maliki, Noval (Tasamuh: Jurnal Studi Islam, 2020)
Radicalism does not only revolve around religious ideology, but the term has been incarnated in social, political and cultural life. Thus it means, any ideology or thought that has a negative effect (side effect) cause someone to be militant and fanatical can be categorized into radicalism. Religious radicalism which has recently surfaced, seems to imply the dissatisfaction of a people in its adaptation to another. This matter concerns the practice of life (mu'amalah) and worship (ubudiyah), especially about the different perspectives on the religion they profess. Different interpretations of seeing a religious law compounded by selfish reasoning leads to harmony elimination in society. Someone who is considered not in accordance with the same understanding, is considered to have deviated from the true teachings of Islam. Then, many influential people called on the people to return to the teachings of the true religion. He considers that he is obliged to straighten out the religious teachings that are bent from the practice of life. Unfortunately, this true teaching is only based on their own understanding. For him, the teachings as understood by him are considered pure and represent the teachings of true and legitimate Islam. If things like this continue, then surely the internal divisions of religious communities will certainly be wide open.